(3GdJaSjQ Gdbhje GdcGTa Yf eYGfi GdbQBf GdcQjes - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s ((3YHO Gddg Hf eMeO Hf jMji Hf eMeO GdbGSe s)
(3ChdgG (B:s
(3JChjd GdMeO ddg QH GdYGdejf , agh GdTcQ ddg hef GdMeO bjd eMehO s
(3BNQgG (B:s
(3hSCdJ Yf QLd JRhL HEeQCI aRfJ bHd Cf jONd HgG , bbdJ Je GdehLhO ef GdcJGH s
(3GdfSNI HgG MhGTs
(3ef Chd GdJaSjQ Zdi ShQI GdTeS ddbGSes
(3hef ShQI GdHdO Edi BNQ GdfGRYGJ dGHf eMeO hef GdfHC Edi GdefGabjf djMi Hf GdMSfj s
(3Ke eSGFd ddbGSe s
(3Ke JaSjQg eeG SCd GdeQJVi ef GdgGOi Yfg EjGg Ke eSGFd SFd YfgG GdCFeI Yf JaSjQ GdeQJVi s
(3Ke eSGFd CLGH YfgG s
Keywords: (3GdJaSjQ hYdhe GdbQBfs